2013
DOI: 10.1007/s11356-013-2121-z
|View full text |Cite
|
Sign up to set email alerts
|

PAH metabolites, GST and EROD in European eel (Anguilla anguilla) as possible indicators for eel habitat quality in German rivers

Abstract: The stock of the European eel (Anguilla anguilla L.) continues to decline and has reached a new minimum in 2011. Poor health status of the spawners due to organic contaminants is one of the possible causes for this dramatic situation. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous contaminants, which are rapidly metabolized in vertebrates. EROD (ethoxyresorufin-O-deethylase) and GST (glutathione-S-transferase) are two enzymes involved in PAH detoxification in fish. In this study, PAH metabolites as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
5
31
0
Order By: Relevance
“…PAH metabolites in bile were determined by the method described by Kammann et al (2014) with modified HPLC conditions. In brief, 25 lL fish bile were mixed with 95 lL water and 5 lL b-glucuronidase/arylsulfatase solution (30-60 U/mL).…”
Section: Methodsmentioning
confidence: 99%
“…PAH metabolites in bile were determined by the method described by Kammann et al (2014) with modified HPLC conditions. In brief, 25 lL fish bile were mixed with 95 lL water and 5 lL b-glucuronidase/arylsulfatase solution (30-60 U/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Van der Oost et al (1994) reported highest 1-OHPyr bile concentrations of approximately 8000 ng/ml (measured by SFS) in eel (Anguilla anguilla) caught in 1991 from freshwater sites near Amsterdam. The mean level of 1-OHPyr in eel collected in 2011 from the river Rhine in Germany near the Dutch border was 3160 ng/ml (measured by HPLC-FL) (Kammann et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…PAH metabolites as biomarker has been determined in a variety of marine, estuarine and fresh water fish species, such as English sole (Collier and Varanasi, 1991), plaice (Richardson et al, 2004), flounder (Ariese et al, 1993;Beyer et al, 1996;Eggens et al, 1996;Kopecka et al, 2006;Vethaak et al, 2011), dab (Kammann, 2007;Vethaak et al, 2009), Atlantic cod (Beyer et al, 1996;Aas et al, 2000), Atlantic hagfish (Sundt et al, 2011), feral finfish (Hellou et al, 2006), eelpout (Tairova et al, 2012), brown bullhead (Yang and Baumann, 2006), trout (Escartín and Porte, 1999a), eel (Van der Oost et al, 1994;Ruddock et al, 2003;Gorbi and Regoli, 2004;Nagel et al, 2012;Kammann et al, 2014), and red mullet (Escartin and Porte, 1999b;Martínez-Gómez et al, 2013). The concentration of PAH metabolites in the bile fluid with dab and flounder as target species has become part of international monitoring programmes, such as the OSPAR Joint Assessment and Monitoring Programme (JAMP) (OSPAR Agreement 2008-09; Technical Annex 2: PAHspecific biological effects monitoring; OSPAR, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has clearly established that the uptake and metabolism of PAHs, as assessed by biliary metabolites in fish exposed in the field or under laboratory conditions, can often be clearly related to PAH contamination of water and sediments (Beyer et al, 2010;Brinkmann et al, 2013;Kammann et al, 2013). The major PAH metabolite in fish bile is 1-hydroxypyrene (1-OH-Pyr) and its conjugated forms, which renders this metabolite a particularly suitable biomarker of exposure to PAHs (Ruddock et al, 2003).…”
Section: Uptake Of Pcdd/fs Pcbs and Pahs From Sediment Suspensionsmentioning
confidence: 99%